Consensus statement on natural orifice transluminal endoscopic surgery and single-incision laparoscopic surgery: heralding a new era in urology? - Gettman, Matthew T. (2008)
[Excerpt] For decades, urologists have implemented technologies that provide effective treatment while limiting morbidity. In many instances, this has been achieved by operating via natural body openings (eg, cystoscopy, transurethral resection, and ureteroscopy) [1,2]. Urologists have also pioneered novel techniques to address clinical situations where access through natural body openings was impossible, such as percutaneous stone surgery, laparoscopy, and robotics [3–5].[...]